Enhancement of Levelwise Cluster Head Selection with the Concept of New Nodes As Cluster Head Nodes - Kaur, Navneet; Saini, Navjeet; Kaur, Sandeep (International Journal of Computer Sciences and Engineering, 2019)
The energy conservation in a network is a key challenge for a protocol, which affects the network for better data communication and scheduling. This paper presents a model which works in levels and in each level. The data distribution and collection in each level are done by CHs. This proposed work will focus on distance based data transmission and load dividing techniques at level 1 between CHs and normal node used as new node concept used as CH node. Which will help to stabilize the network by maximizing the lifespan of the network. The objectives of the work is to implement reclustering, multihop data transmission processes model and data distribution model by minimizing the packet loss accomplishing the load divide technique at level 1 among nodes.